Analisis Textbook Olahraga di Sekolah Menengah Pertama (SMP) Dari Tinjauan Perspektif Gender - Alimin Hamzah; Muh. Ilham Aksir (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2022)
The purpose of this study is to examine how gender is applied in textbooks used in junior high schools (SMP) in the subject of Physical Education. In this study, the author uses a case study design approach which is used to examine social reality and requires in-depth exploration. This research was conducted in one city in Indonesia involving 4 schools. Semi-structured interviews were used to collect data with the number of participants being 4 sports teachers who taught using the textbook. During the interview process, we recorded it so that it could be played over and over again so that it could be analyzed. The findings of this research reveal that there is a gender bias in schools in Indonesia based on the textbook. As for suggestions in this study, the government should restructure sports textbooks based on studies of anatomy and physiology so that students receive equal rights to explore themselves in the field of sports and opportunities to give birth to talented athletes not only for male students but also for female students.